A new species of land flatworm (Platyhelminthes: Continenticola) from areas of Araucaria Forest in southern Brazil - Rossi, Ilana; Fontoura, Marcela; Amaral, Silvana; Leal-Zanchet, Ana M. (Zootaxa, 2014)
The genus Cratera Carbayo et al. was proposed to encompass five species of Geoplaninae from southeastern Brazil that were mainly recorded in the state of São Paulo. Here we describe a new species of the genus, C. steffeni sp. nov., that occurs in areas of Araucaria Forest in southern Brazil, which augments the known distribution of Cratera. The new species is distinguished from others of the genus by its characteristic colour pattern and a combination of internal morphological characters.